The Link Between Breastfeeding & Asthma – Tenuous or Trustworthy - Lim, Benji; McCormack, Ruaidhrí; O’Loughlin, Clare; Ramphul, Meenakshi; Sehmer, Benjamin (Trinity Student Medical Journal, 2007)
Aim: The primary aim of this review was to examine the evidence for and against breastfeeding as a protective factor in the development of asthma in childhood. Methods: A literature search was carried out using the PubMed database, yielding 304 papers between the dates of 1-Jan-1999 and 2-Feb-2007. An English language restriction was imposed. Reviewers assessed study quality and extracted data. Relevant data were obtained from Irish, European and international bodies with respect to asthma, the percentage of mothers breastfeeding, and current recommendations for breastfeeding. Results: The prevalence of childhood asthma in Ireland is estimated to be 15%, and approximately 30% of children under the age of five have had at least one attack of asthma2. Approximately one in three Irish mothers breastfeed, at least initially, and amongst this group 36% did so exclusively3. A number of constituents of breastmilk have been proposed to decrease the risk of asthma, including CD14 and omega fatty acids. A 1995 prospective follow-up study reported that exclusive breastfeeding of greater than one month’s duration resulted in a significant reduction in respiratory allergy at age seventeen4. Of the four randomized controlled trials (RCTs) analyzed in this review, two reported that exclusive breastfeeding, of at least four months duration, significantly reduced the risk of childhood asthma 5,6. A third RCT found no evident link between breastfeeding and asthma7, while the final RCT reported that breastfeeding may in fact increase the risk of asthma8. Conclusion: Given the genetic and environmental variables at play in the phenotypic expression of asthma as a disease, the relationship between breastfeeding and asthma is still somewhat unclear. Four high-quality RCTs yield conflicting results. The World Health Organisation (WHO) and the Department of Health and Children in Ireland both recommend breastfeeding for the first six months of life9,10. These evidence-based recommendations consider the benefits of breastfeeding, including reducing the risk of asthma.